Risk Factors and Outcomes of Low Birth Weight Neonates Admitted In a Tertiary Care Center - Adhikari, Jyoti; KC, Rajesh; Kharel, Shristi (Journal of Nepalgunj Medical College, 2020)
Introduction: Birth weight <2500 grams, <1500 grams and <1000 grams irrespective of gestational age is low birth weight, very low birth weight and extremely low birth weight respectively. Low birth weight is associated with high morbidity and mortality. Aims: To find out the possible maternal risk factors associated with low birth weight babies, morbidities and mortalities seen in them during their hospital stay. Methods: Hospital based cross sectional observational study was performed in 200 newborns <2500 grams in Nepalgunj Medical College, Kohalpur, Banke, Nepal. Results: Out of 200 neonates 8 (4%), 40 (20%) and 152 (76%) were extremely low birth weight, very low birth weight and low birth weight respectively with Male:Female ratio of 1.12:1. Most common maternal risk factors for low birth weight was Illiterate mothers (88%) followed by preterm delivery (68%). Inadequate antenatal visit was associated with low birth weight (P<0.05). Most common morbidity seen in low birth weight was neonatal sepsis (96%) followed by neonatal jaundice (87%). 44 (22.0%) neonates expired and 156 (78.0%) survived. Neonatal sepsis was most common (36.4%) cause of mortality followed by respiratory distress syndrome (22.7%). Conclusion: Certain measures could be taken to prevent low birth weight deliveries: discouraging delivery at teenage, adequate antenatal visits, avoiding smoking and alcohol during pregnancy. Well trained staffs and better facilities in neonatal intensive care unit could improve the survival and minimize the morbidities in low birth neonates.